2018
DOI: 10.1021/acs.jnatprod.7b01070
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor (ER) Subtype Selectivity Identifies 8-Prenylapigenin as an ERβ Agonist from Glycyrrhiza inflata and Highlights the Importance of Chemical and Biological Authentication

Abstract: Postmenopausal women are increasingly using botanicals for menopausal symptom relief due to the increased breast cancer risk associated with traditional estrogen therapy. The deleterious effects of estrogens are associated with estrogen receptor (ER)α-dependent proliferation, while ERβ activation could enhance safety by opposing ERα effects. Three medicinal licorice species, Glycyrrhiza glabra (G. glabra), G. uralensis, and G. inflata, were studied for their differential estrogenic efficacy. The data showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…5B). Other studies suggest that GI has superior chemopreventive properties to GG (11)(47). GI had the greatest anti-inflammatory activity among medicinal licorice species in macrophage cells because it contains two major anti-inflammatory compounds, LicA and LigC (11).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5B). Other studies suggest that GI has superior chemopreventive properties to GG (11)(47). GI had the greatest anti-inflammatory activity among medicinal licorice species in macrophage cells because it contains two major anti-inflammatory compounds, LicA and LigC (11).…”
Section: Discussionmentioning
confidence: 96%
“…GI had the greatest anti-inflammatory activity among medicinal licorice species in macrophage cells because it contains two major anti-inflammatory compounds, LicA and LigC (11). Also, GI contains the ERβ preferential agonist 8-prenylapigenin (47), which may have a better safety profile. Long-term studies are planned to compare the effect of GG and GI on E 2 -induced mammary carcinogenesis in ACI rats and ultimately estrogen metabolism in women.…”
Section: Discussionmentioning
confidence: 99%
“…8-Prenylnaringenin showed nanomolar estrogenic RP without ER selectivity ( Hajirahimkhan et al, 2013 ). A recent study identified 8-Prenylapigenin from Glycyrrhiza inflata as an ERβ agonist ( Hajirahimkhan et al, 2018 ).…”
Section: Other Estrogenic Plantsmentioning
confidence: 99%
“…ex DC differ significantly in the ratio of liquiritigenin to isoliquiritigenin, as well as in congeneric constituents, and are therefore expected to have different bioactivities. 122,123 Characterization sufficient for the detection of such minor components, known or unknown, is therefore critical for quality control and for monitoring batch-to-batch variation and stability. 15,124 Identity and purity of all materials used, regardless of the supplier, should be verified prior to use.…”
Section: Np Specifications and Integritymentioning
confidence: 99%